PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PERKEBUNAN SAWIT DI DESA TEUPIN PANAH, KECAMATAN KAWAY XVI KABUPATEN ACEH BARAT - Badli, Saiful; Syahril, Syahril; Noviar, Helmi; Mardaleta, Mardaleta; Nasir, M. (Jurnal Pengabdian Agro and Marine Industry, 2024)
Agriculture and plantations in Indonesia are very worthy of competing to seize market opportunities in the era of free trade. in this Community Service (PKM) activity, holding and providing counseling to the Teupin Panah,Kecamatan Kaway XVI Aceh Barat. preparing facilities and locations to carry out activities. the goal is that the expected results are useful and beneficial and also right on target for the community and designing a schedule, the first stage was carried out in May 2023, and June 11, 2023. lecture and discussion methods. economic empowerment by forming cooperatives and savings and loans, added value for the community by processing oil palm fronds into fertilizer, and the leaves can be used to weave mats, and no less importantly, ribs can be used as handicrafts. By carrying out Community Service activities, it is beneficial for academics. especially the knowledge that is directly obtained and provides a real contribution to the community in increasing income.